Device for Measuring Driving Suitability and Blue Light Protection in Sunglasses - Loureiro, Artur; Ventura, Liliane (Revista Brasileira de Física Médica, 2022)
Sunglasses safety plays an important role for the wearer and most when choosing their sunglasses do not consider some important features. Among other relevant tests, sunglasses should have properties that do not negatively interfere with the user’s vision when driving land vehicles. Testing sunglasses for transmittance of total visible light and traffic lights are requirements of the sunglasses standard ISO12312-1. We have developed a prototype for users to self-check their sunglasses for traffic lights regarding the safety for driving. The prototype consists of an illumination source and a detection photosensor that yield four transmittance values weighted with different functions. Combining the values of the four outputs of the sensor, it is possible to provide luminous bands quite similar to the required from the standards regarding the visible spectrum and traffic light transmittances. The Q factors required on the standards evaluate the color distortion for the vision on sunglasses and are measurements provided by the prototype. The luminous transmittance and Q factors for 60 sunglasses lenses were measured in a gold standard and were used for evaluating our prototype. Bland-Altman analysis presented non-significant biases and narrow 95 % limits of agreement within pre-defined tolerances, for all measurements. The results show that the prototype is a worthwhile alternative for providing the public with access to their own sunglasses' information on driving suitability, as well as for industry and retailers for quick verification of their products. This work is potentially significant in educating the public about some features to consider before purchasing sunglasses and in providing the public with a means to self-test their sunglasses regarding their quality and driving safety. It is also a wake-up call for the sunglasses industry and retailers to be aware of the quality of sunglasses on the market with respect to the driving safety of users.